KERAGAMAN JUMLAH ANAK SEKELAHIRAN DAN BOBOT LAHIR BANGSA BABI GALUR MURNI AUSTRALIA (Litter Size and Birth Weight Variances of Australian Pure Breed Swine) - Eva Diana Damanik (Universitas Sumatera Utara, 2013)
ABSTRACT Swine is a business-majority of districts Siborong borong, where most of the sources livestock derived from livestock breeding centers, so that must be known that there is a great variety among the breed of swines and then obtained the greatest most superior of superior livestock to increase the productivity of swine pure breed. This research was conducted at the livestock breeding centers Swine and Buffaloes Installation Sinur, Siaro village Siborong-borong starting in May-September 2012 using a survey method. Material used were direct observational piglets data from May to September 2012 (primary data) and piglets recording data time series ranging from 2009 through 2011 (secondary data). Breed used were Landrace, Yorkshire, Duroc and Berkshire as much as 10 head sows per breed. Parameters measured were variance, the litter size and birth weight. The Results showed that the variances of litter size and birth weight Australian pure breed swine between in medium to high every year. The greatest variance range mean values ​​found in Duroc breed about 0.1 for birth weight (coefficient variances ± 19,48%) and 7.73 for litter size (coefficient variances ± 35,77%). The best kinds of swine can be used as breeding is Yorkshire breed because it have litter size per birth very high and nature of parental (mothering ability) is good and kind of breed that can be considered to selected is Duroc breed. Keywords: Variance, litter size and birth weight